The Usage of Password Generators to Enhance Data Security in Most Used Applications - Erwin Halim; Angelia Hartanto Teng; Marylise Hebrard; David Sundaram; Placide Poba-Nzaou (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
One of the world's global issues is data breaches. These crimes can happen because most people use hackable passwords such as their birthdates and sequencing numbers or alphabets so they would not be easily forgotten. Setting weak passwords in almost or all accounts certainly raises issues and increases the possibility that classified information is hacked and leaked. When it happens, classified data can be misused and taken advantage. This research will help spread awareness to society on how important data security is and how helpful password generators can be to reduce and prevent the probability of data security crimes from happening. This quantitative research uses SMART-PLS as a statistical tool to process the data gathered and random sampling to determine its population. SMART-PLS is variance-based structural equation modeling that uses the partial squares path modeling method. Overall, researchers successfully gathered 114 datasets. Google Forms was used to gather the data. A potential limitation of the study is that all respondents are primarily based in Jakarta. Expanding the geographic focus for further study to gain more insights is highly recommended. 48% of the respondents came from the age group of under 20, occupation as students. Factors significantly affecting people's intention to comply with password generators are perceived password effectiveness, perceived ease of use, subjective norms, and attitude. Eventually, the intention to comply may arouse actual compliance. The result of the study can be used to raise educational campaigns on the usefulness of password generators to promote data security. Based on the result, 78.9% of the respondents are willing to increase their data security. This research contribution is to see how aware people are of data security, how well they know password generators as a technology to generate strong passwords, and how welcome they are with the idea of using password generators.